Assessing Waste Management and Green Technology Adoption in Enhancing Sustainable Tourism at Jabal Arafah Mosque Batam Indonesia - Lapotulo, Nensi; Wardani, Yudha; Pristiwasa, I Wayan Thariqy Kawakibi; Sukmamedian, Haufi; Hardini, Widi; Cherryline, Violetta; Fransiska, Mischella (Industrial and Domestic Waste Management, 2025)
The rapid growth of religious tourism contributed to increased economic and social activities but also created environmental pressures, particularly related to increased waste volume and resource use in spiritually based tourist destinations. Jabal Arafah Mosque (MJA) in Batam City, as an icon of religious tourism, faced challenges in maintaining environmental sustainability due to the high intensity of visits. In contrast, empirical studies integrating waste management and the adoption of green technology within religious tourism were still limited. This study aimed to analyse the partial and simultaneous effects of waste management implementation and green technology adoption on sustainable tourism performance at MJA. The study used a quantitative, causal-associative design involving 50 respondents, including managers, operational officers, stakeholders, traders, and visitors. Data collection was carried out using a structured questionnaire, and the data were analysed using multiple linear regression in SPSS. The analysis results showed that the implementation of waste management (β = 0.562; p < 0.001) and the adoption of green technology (β = 0.368; p = 0.005) had positive and significant effects on sustainable tourism performance, with waste management as the dominant variable. The model explained 75.8% of the variation in sustainable tourism performance (R² = 0.758). These findings confirmed that strengthening a structured waste management system, supported by the implementation of green technology, was a key strategy for improving environmental sustainability and the quality of management of religious tourism destinations.